Extended store How digitalization effects the retail space design - Barbara, Anna (Design International, 2021)
Extended store has been a work of mapping the phenomena of digitalization that effects spaces and above all the world of retail. Apps allow interaction between users and brands, the book hosts a selection of those which are redesigning spaces, changing their forms, hierarchies, flow systems, arrangement of goods, experiences, and dimensions. The store takes on completely new dimensions and characteristics, in addition to sales, that of exhibition, performance, entertainment, engagement and sensory immersion. The store is a place tailored to the desires and sensory, psychological, and temporal needs of those who want to encounter the brand. The extended store will be a shop spread throughout the territory, it will be more connected, more available, more open and at the same time closer, mass customized, but above all it will be more digitalized and able to fulfil and modify itself more quickly and faithfully to needs and desires. Shops will not disappear in the 21st century, but they will have to change (if they have not already done so) to survive. They will have to evolve by integrating technological solutions that are not only back-end (as they have done so far), but front-end, and therefore available to customers in the shop as in the cases reported in the book.